Expansion of a Telomeric FLO/ALS-Like Sequence Gene Family in Saccharomycopsis fermentans - Beatrice Bernardi; Yeseren Kayacan; Jürgen Wendland (Frontiers in Genetics, 2018)
Non-Saccharomyces species have been recognized for their beneficial contribution to fermented food and beverages based on their volatile compound formation and their ability to ferment glucose into ethanol. At the end of fermentation brewer’s yeast flocculate which provides an easy means of separation of yeasts from green beer. Flocculation in Saccharomyces cerevisiae requires a set of flocculation genes. These FLO-genes, FLO1, FLO5, FLO9, FLO10, and FLO11, are located at telomeres and transcription of these adhesins is regulated by Flo8 and Mss11. Here, we show that Saccharomycopsis fermentans, an ascomycete yeast distantly related to S. cerevisiae, possesses a very large FLO/ALS-like Sequence (FAS) family encompassing 34 genes. Fas proteins are variable in size and divergent in sequence and show similarity to the Flo1/5/9 family. Fas proteins show the general build with a signal peptide, an N-terminal carbohydrate binding PA14 domain, a central region differing by the number of repeats and a C-terminus with a consensus sequence for GPI-anchor attachment. Like FLO genes in S. cerevisiae, FAS genes are mostly telomeric with several paralogs at each telomere. We term such genes that share evolutionary conserved telomere localization “telologs” and provide several other examples. Adhesin expression in S. cerevisiae and filamentation in Candida albicans is regulated by Flo8 and Mss11. In Saccharomycopsis we identified only a single protein with similarity to Flo8 based on sequence similarity and the presence of a LisH domain.